The resolution of poverty and cultural marginalisation in Zimbabwe through a dynamic educational system - Muzvidziwa, Irene (2016)
This essay focuses mostly on the Zimbabwean experience. Poverty reached endemic levels in Zimbabwe during the first decade of the twenty first century partly due to economic mismanagement and the devastating effects of western backed economic sanctions.Education is touted as one of the key factors that can contribute to poverty reduction,minimising of social exclusion and social marginalisation. Zimbabwe once a buoyant middle income country is characterised by growing poverty', inequality, and lack of effective utilisation of resources. To many education is the answer to these social ills. Education for some has the ability' to play a positive role in reducing HIV and AIDS, poverty and growing social inequality.